Arqueología de la música : gaita, órgano hidráulico y otros instrumentos musicales romanos de Bracara Augusta (Braga, Portugal) - Morais, Rui; Sousa, Maria José; Salido Domínguez, Javier (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
The archaeological excavation work carried out in recent years at Braga, the ancient Roman city of Bracara Augusta, have located several remains corresponding to musical instruments. In this article we thoroughly analyze the representations made on a local roman oil lamp terracotta, corresponding to unusual instruments in Hispania, such as organum hydraulicum or hydraulis (water organ) and tibia utricularis (bagpipe). Also we study in context a ceramic fragment of a bucina or tuba and several percussion and wind instruments made of metal, named as cymbala and tintinnabula that inform us about the musical life in ancient Bracara Augusta. In addition to musical instruments, an interesting piece of painted pottery locally produced shows us a dance or ritual dance which refers to specific scenes that happened in the city in close link with the instruments analyzed above.